Food access and diet quality are associated with quality of life outcomes among HIV-infected individuals in Uganda - Palermo, Tia; Rawat, Rahul; Weiser, Sheri D.; Kadiyala, Suneetha (Public Library of Science, 2013)
Background Food insecurity is associated with poor nutritional and clinical outcomes among people living with HIV/AIDS. Few studies investigate the link between food insecurity, dietary diversity and health-related quality of life among people living with HIV/AIDS. Objective We investigated whether household food access and individual dietary diversity are associated with health-related quality of life among people living with HIV/AIDS in Uganda. Methods We surveyed 902 people living with HIV/AIDS and their households from two clinics in Northern Uganda. Health-related quality of life outcomes were assessed using the Medical Outcomes Study (MOS)-HIV Survey. We performed multivariate regressions to investigate the relationship between health-related quality of life, household food insecurity and individual dietary diversity. Results People living with HIV/AIDS from severe food insecurity households have mean mental health status scores that are 1.7 points lower (p<.001) and physical health status scores that are 1.5 points lower (p<.01). Individuals with high dietary diversity have mean mental health status scores that were 3.6 points higher (p<.001) and physical health status scores that were 2.8 points higher (p<.05). Conclusions Food access and diet quality are associated with health-related quality of life and may be considered as part of comprehensive interventions designed to mitigate psychosocial consequences of HIV.